2020
DOI: 10.1186/s13717-020-00263-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling fire ignition probability and frequency using Hurdle models: a cross-regional study in Southern Europe

Abstract: Background Wildfires play a key role in shaping Mediterranean landscapes and ecosystems and in impacting species dynamics. Numerous studies have investigated the wildfire occurrences and the influence of their drivers in many countries of the Mediterranean Basin. However, in this regard, no studies have attempted to compare different Mediterranean regions, which may appear similar under many aspects. In response to this gap, climatic, topographic, anthropic, and landscape drivers were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…On the contrary, olive groves show lower burnt area rates even when this land use is widespread in the case study. These results are supported by D'Este et al [83].…”
Section: Fire Severity Classificationsupporting
confidence: 79%
“…On the contrary, olive groves show lower burnt area rates even when this land use is widespread in the case study. These results are supported by D'Este et al [83].…”
Section: Fire Severity Classificationsupporting
confidence: 79%
“…Nevertheless, in our study, surprisingly no significant differences were detected among subgroups on the perception of importance of scientific research and community involvement in improving and spreading awareness of wildfire risk. In fact, previous results have revealed that forest experts consider public awareness, in particular, concerning the impact of human activities, as a crucial element for risk reduction and fire management, especially in view of the ensuing effects of climate change [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The geomorphological variables (Slope, Elevation, and Easterness) showed lesser importance in estimating the 1-h fuel load, probably due to their relationship to the landscape topography rather than to vegetation. According to D'Este et al [41], fire ignition probability is high at an altitude of about 500 m, which is the mean value of elevation in Apulia. This confirms the poor predictive power of these variables in discriminating the fire occurrence and the fine dead fuel production.…”
Section: Discussionmentioning
confidence: 98%
“…The fire season coincides with the summer period. Typically, the number of wildfires slightly increases between May and June, reaching a peak in August; these fires are mainly related to human activity [40,41]. Martina Franca represents one of the main towns in the Itria Valley, located in the central-south part of Apulia.…”
Section: Study Areamentioning
confidence: 99%